About bridges between law and public management concepts - Sześciło, Dawid (Journal of Public Governance, 2013)
Post bureaucratic concepts of public management, such as new public management and governance reshaped not only theoretical but also practical landscape of public administration, at a global scale. These two mainstreams of reforms originated from non-legal view on the administration, which was the key feature of Weberian bureaucracy. Legal approach to administration, in the light of the expansion of economic, managerial and sociological theories of public administration reform, faces the necessity to develop a coherent response to the recommendation of non-legal models of public management. The article outlines the theoretical concept of incorporating the law perspective in the mainstream debate on the reform of public administration. It is based on the assumption that the theory of law and the legislation have to fulfill two basic functions: 1) protective – protect the constitutional values and rights in the process of reforming the administration and 2) instrumental – to provide the necessary equipment for the effective implementation of the public management reforms.